Study about Upper Limb Fractures in Adolescents Attending Selected Government Hospitals in Sri Lanka and Its Associated Prehospital Care - Jayasekera, Hemali; Siritunga, Samitha; Senarath, Upul (Issues and Development in Health Research Vol. 5, 2021)
Injuries are the number one cause for morbidity and mortality among adolescents. Adolescent fractures are a hidden public health problem in Sri Lanka. Injury to upper limb will affect all the activities of the adolescent in this new era as risk factors of upper limb fractures are common with highly commercialized society. Prevention of adolescent injuries is an investment for the country as they belong to economically productive age group. To ease the burden on the state, attention should be given for prehospital care. Objective of the Study: The objective of the study was to describe the sociodemographic factors of adolescents with upper limb fractures in a district in Sri Lanka and associated prehospital care. Methods: A hospital based descriptive cross-sectional study was conducted on a sample of 1090 newly diagnosed adolescents with upper limb fractures aged 10 to 19 years treated from higher-level hospitals in the district of Colombo. Descriptive statistics were used to describe sociodemographic details and the prehospital care methods. Results of the Sample: The mean age of the sample was 12.45 years (SD=2.59). The majority were males (n = 892; 81.8%). Adolescent’s residence (n=518, 47.5%) was the commonest place of injury. Most of the adolescents (n=855, 78.5%) sustained upper limb fractures following a fall. The majority used three-wheeler taxi as transportation method to reach the hospital (n= 687; 63%). Out of the participants, only 29.5% (n= 322, CI: 26.8-32.3) received any kind of prehospital care. Conclusion: Most of the adolescents had not received any kind of prehospital care and their transportation method to a health care setting was three-wheeler taxis. Adolescents belong to a productive age group and are in the transition period from childhood to adulthood, so conducting awareness programs among school children, their parents, and teachers will benefit the country.